2020
DOI: 10.31925/farmacia.2020.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pesticide Residues and Heavy Metals Content in Various Peppermint Samples

Abstract: Taking into consideration, that peppermint tea is frequently used in phytotherapy due to its wide range of therapeutic effects, ten samples of peppermint leaves were analysed in order to assess the level of pesticide residues and heavy metals. Pesticide residues were under the detection limit for six samples. However, in four peppermint samples we have determined λcyhalothrin (42-45 µg/kg), chlorpyrifos-ethyl (20-43 µg/kg), and cyfluthrin (78 ± 21 µg/kg), in concentrations below the maximum residues limits. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These HMs can cause toxicity if their allowable levels are surpassed [3] . The HMs are non-biodegradable and may amass in the ecosystem reaching unsafe proportion for human health [4] , [5] . Besides raw sources of water, water packaging materials have become major sources of contaminants in bottled and sachet water [3] .…”
Section: Introductionmentioning
confidence: 99%
“…These HMs can cause toxicity if their allowable levels are surpassed [3] . The HMs are non-biodegradable and may amass in the ecosystem reaching unsafe proportion for human health [4] , [5] . Besides raw sources of water, water packaging materials have become major sources of contaminants in bottled and sachet water [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of metal ions in soil may have beneficial effects on vegetation development, or may have toxic effects on soil biology by affecting the biochemical processes that occur in the soil, depending on their type [5,16]. Interestingly, recent research on spices and medicinal plants from the South-East region of Romania indicated that wild-growing plants found near industrial areas can accumulate iron and copper in variable amounts, in certain cases the values exceeding the limits imposed within EU [9,16]. Therefore, a proper assessment and monitoring of the soil would greatly increase the quality of the edible and medicinal plants.…”
Section: Resultsmentioning
confidence: 99%
“…The pollution of the environment with heavy metals, including copper, is a major problem worldwide [9,16,18,21,23]. Enzymatic reactions are inhibited in soil microbiota by metals through several mechanisms, such as: complexation of the substrate, combination with the active protein groups of the enzymes and reaction with the enzyme-substrate complex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations